Endoscopic variceal ligation combined with carvedilol versus endoscopic variceal ligation combined with propranolol for the treatment of oesophageal variceal bleeding in cirrhosis: study protocol for a multicentre, randomised controlled trial - Jing Wang; Meng Li; Lei Wang; Li Zhang; Ling Yang; Jian Wang; Duolao Wang; Rong Wang; Ya Peng; Chao Ma; Yiling Li; Yi Chen; et al. (BMJ Open)
Introduction Liver cirrhosis and its severe complication, oesophageal variceal bleeding (EVB), pose significant health risks. Standard treatment for EVB combines non-selective beta-blockers (NSBB) with endoscopic variceal ligation (EVL). Carvedilol, an NSBB with additional benefits, is preferred for compensated cirrhosis. However, no randomised controlled trial (RCT) has compared carvedilol with propranolol, a conventional NSBB, in combination with EVL for secondary prophylaxis. This study aims to compare the effectiveness and safety of these treatments in preventing variceal rebleeding or death in patients with cirrhosis and EVB.Methods and analysis This multicentre, RCT is scheduled to begin in December 2024, with recruitment and follow-up continuing until December 2026. Eligible participants are patients with liver cirrhosis and EVB. Participants are randomly assigned in a 1:1 ratio to receive EVL combined with either carvedilol or propranolol. The primary endpoint is the incidence of variceal rebleeding or all-cause death. Secondary endpoints include all-cause death, liver-related death, each of the complications of portal hypertension (overt ascites, overt hepatic encephalopathy, spontaneous bacterial peritonitis, hepatorenal syndrome, portal vein thrombosis), hepatocellular carcinoma, changes in liver function (assessed by Child-Pugh and Model for End-Stage Liver Disease scores), changes in liver stiffness, changes in spleen stiffness, and adverse events. Subgroup and sensitivity analyses will be conducted to evaluate the consistency and robustness of the treatment effects. A total sample size of 524 patients (262 per group) is required to detect a significant difference between the treatment arms.Ethics and dissemination The study protocol has been approved by the ethics committee of the First Hospital of China Medical University (No. 2024-656-2). The study will follow the Declaration of Helsinki and Good Clinical Practice guidelines. The findings of this trial will be disseminated through peer-reviewed publications, conference presentations and healthcare professionals to guide future clinical practice.Trial registration number Chinese Clinical Trial Registry (Registration number: ChiCTR2400089692).